PENGARUH KOMITMEN ORGANISASI, KOMPETENSI APARATUR, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP IMPLEMENTASI SAKIP DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Fatinaya Mardha, Salsabila; Hardi Raharjo, Teguh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the effect of organizational commitment, apparatus competence, and information technology utilization on the implementation of SAKIP at the Population and Civil Registration Office. The method used is a quantitative approach with an associative design and a confirmatory research design. Data collection was conducted via a questionnaire. The study population consisted of 125 employees of the Population and Civil Registration Offices in Pati and Jepara Regencies, with a sample of 76 respondents selected using convenience sampling. The collected data were analyzed through multiple linear regression, partial and simultaneous hypothesis testing, as well as coefficient of determination analysis using IBM SPSS version 25. The findings indicate that organizational commitment has a positive but insignificant effect on the implementation of SAKIP. Conversely, apparatus competence and the use of information technology significantly and positively influence the implementation of SAKIP. Collectively, the three independent variables explain 50.1% of the variance in SAKIP implementation of SAKIP, with an F-calculated value (24.073) > F-table value (2.732) and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.501 indicates that the three variables account for 50.1% of the variation in SAKIP implementation, whereas the remaining percentage is explained by variables beyond the scope of this study.